Self-reported and activPALTM-monitored physical activity and sedentary behaviour in college students: Not all sitting behaviours are linked to perceived stress and anxiety. Issue 13 (2nd July 2020) - Felez-Nobrega, Mireia; Bort-Roig, Judit; Briones, Laia; Sanchez-Niubo, Albert; Koyanagi, Ai; Puigoriol, Emma; Puig-Ribera, Anna
ABSTRACT: This study examined relationships between physical activity (PA) and sedentary behaviour (SB) with state-trait anxiety and stress. State-Trait anxiety (State-Trait Anxiety Inventory), psychological stress (Perceived Stress Scale), SB across domains during weekdays and weekends (Last 7-day Sedentary Behaviour Questionnaire) and PA intensities (International Physical Activity Questionnaire) were assessed by self-report in 360 undergraduates (44% females, mean age 20.9 ± 2.93 years). A subsample (n = 121; 53.7% females; mean age 20.8 ± 2.6 years) wore an activPAL TM to determine total SB, light, and moderate-to-vigorous intensity PA (MVPA). Self-reported MVPA was significantly associated with lower trait anxiety and perceived stress, whereas light PA was only associated with lower perceived stress. Weekend total self-reported SB was related to higher trait anxiety and perceived stress levels, while total SB during the week was not. Of all SB domains, only leisure SB (screen and non-screen based) was associated with higher trait anxiety and perceived stress. PA attenuated the negative relationships between excessive sitting time and trait anxiety but not perceived stress. No associations were found for monitor-based measures of PA and SB. No associations were found between PA or SB variables with state anxiety. Further research is needed to assess causal and reciprocal relationships between PA, SB and mental health in college students.